Az ima szerepe a vallástanár mentális egészsége szempontjából - Gabriella Márta GORBAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Role of Prayer Regarding the Religion Teacher’s Mental Health.